Metal-to-ligand charge-transfer sensitisation of near-infrared emitting lanthanides in trimetallic arrays M2Ln (M=Ru, Re or Os; Ln=Nd, Er or Yb). - Pope, S; Coe, B; Faulkner, S; Laye, R (2005)
The new pro-ligand 4-methyl-4'-(carbonylamino(2-(tert-butoxycarbonylamino)ethyl))-2,2'-bipyridyl (L1) has been prepared and used to synthesise the complex fac-Re(I)Cl(CO)3(L1) 1 and the complex salts [M(II)(bipy)2(L1)](PF6)2 (M=RuII 8 or OsII 15). Deprotection with trifluoroacetic acid affords the amine-functionalised derivatives fac-Re(I)Cl(CO)3(L2) 2, [M(II)(bipy)2(L2)](PF6)2 (M=RuII 9 or OsII 16) which react with the dianhydride of diethylenetriamine pentaacetic acid (DTPA) to give the binuclear complex {fac-Re(I)Cl(CO)3}2(L3) 3 and the complex salts [{M(II)(bipy)2}2(L3)](PF6)4 (M = RuII 10 or OsII 17). The latter react with salts Ln(OTf)3 to afford a series of 12 heterotrimetallic compounds that contain a lanthanide (Ln) ion in the DTPA binding site; {fac-Re(I)Cl(CO)3}2(L3)LnIII (Ln=Nd 4, Er 5, Yb 6 or Y 7) and [{M(II)(bipy)2}2(L3)LnIII](PF6)(OTf)3 (M=RuII, Ln=Nd 11, Er 12, Yb 13 or Y 14; M=OsII, Ln=Nd 18, Er 19, Yb 20 or Y 21). All of these trimetallic species display absorption bands ascribed to metal-to-ligand charge-transfer (MLCT) excitations, and luminescence measurements show that these excited states can be used to sensitise near-infrared emission from LnIII (Ln=Nd, Er or Yb) ions. Single crystal X-ray structures of L1 and [RuII(bipy)2(L2H)](H2PO4)3.(CH3)2CO.0.8H2O were obtained, the latter revealing the presence of H2PO4- counter anions, the source of which is presumed to be hydrolysis of PF6- ions.